Advances in Mechanical Engineering : Selected Contributions from the Conference 'Modern Engineering: Science and Education', Saint Petersburg, Russia, May 2018 /: Selected Contributions from the Conference 'Modern Engineering: Science and Education', Saint Petersburg, Russia, May 2018. (2019) - Unknown
No abstract available